Implikasi Hukum Perlindungan Sementara (Injunction) terhadap Persaingan Usaha Negatif dalam Berita Media Online di Indonesia - FIKI RACHMAN (Jurnal Hukum Lex Generalis, 2026)
This research examines the legal implications of injunctions on negative business competition in online media news in Indonesia. The background arises from the rapid growth of digital media, which has fueled unhealthy practices such as black campaigns, hoaxes and paid news, which damage the reputations of business actors and disrupt a healthy competitive climate. This phenomenon is difficult to control with conventional regulations due to the rapid virality and irreparable nature of digital content. The research problem formulation includes three questions: (1) the legal implications of injunctions in stopping the spread of negative business competition news; (2) the balance between protecting the reputation of legal entities and freedom of the press and expression; and (3) the mechanism for implementing injunctions in Indonesia. The framework is based on the theory of restorative justice, legal certainty (lex certa) and proportionality of rights restrictions, harmonized with Pancasila and the 1945 Constitution. The research is normative-juridical with a descriptiveanalytical approach, utilizing primary, secondary and tertiary legal materials. The conclusion states that injunction is an effective, preventive and responsive instrument to prevent irreparable losses, balances the protection of reputation rights proportionally with press freedom and has a clear implementation mechanism through civil courts that aligns with Law No. 5 of 1999, the Press Law and Supreme Court regulations. The research findings are expected to provide policy recommendations for the Commission for the Public Commerce and Industry (KPPU), the courts and media practitioners.